The long(er)-term impacts of Chile Solidario on human capital and labour income - Guido Neidhöfer; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper examines Chile Solidario, a social protection programme that provides poor households in Chile with preferential access to a conditional cash transfer programme designed to facilitate investments in children's health and education. We assess the programme's longer-term impact on educational attainment and labour income at ages 25-28. Overall, Chile Solidario has a positive and long-lasting effect, albeit with significant impact heterogeneity. The effects on educational attainment are similar for women and men, and for indigenous and non-indigenous people, but the effects on labour income are driven by men and non-indigenous people. The impact on labour income is not significantly different from zero for women with children, but is positive and significant for women without children. The effects on both education and labour income are concentrated in urban areas. Our results indicate that the impact of Chile Solidario depends on societal and structural factors underpinning labour markets in Chile.
Keywords: I21; I38; J24; O15; 330; Conditional cash transfers; human capital; labour income; children; Latin America; Chile Solidario